Pancreaticoduodenectomy for paediatric pancreatic trauma with a decade of follow-up - Madhav D Thatte; Dhananjay Vaze (Wolters Kluwer Medknow Publications, 2014)
Pancreaticoduodenal injuries are rare in children. They pose challenges for the treating surgeon in decision making with respect to diagnosis, surgical and post-surgical management. The management plan must be tailored to the nature and severity of trauma, patient profile, surgeon's expertise and the resources available at surgeon's disposal. We describe a pancreaticoduodenal injury in 3-year-old child with successful outcome and follow-up of a decade.